Sex differences in the effects of Auricularia auricula-judae ethanolic extracts on the life span of Drosophila melanogaster during stress and non-stress conditions - JC James N. Romero, Ma. Rosario Rufina E. Ramos, Ourlad Alzeus G. Tantengco, Paul Mark B. Medina (Journal of Applied Pharmaceutical Science, 2018)
Antioxidant enzymes can help to increase the life span of flies by allowing the organisms to adapt during the stressful conditions. Edible mushrooms are good sources of antioxidant compounds. Auricularia auricula-judae, locally known as “tenga ng daga” is a popular edible mushroom in the Philippines. We investigated the effects of chronic supplementation of wild and cultivated A. auricula-judae crude ethanolic extracts in the life span of adult Drosophila melanogaster in the presence and absence of environmental stress such as thermal stress and starvation stress. 2,2-diphenyl-1-picrylhydrazyl assay revealed a higher antioxidant activity of cultivated A. auricula-judae crude ethanolic extract (CAEE) compared with wild A. auricula-judae crude ethanolic extract (WAEE). WAEE had no effect on the life span of female flies but it increased the life span of male flies. CAEE decreased the life span of both male and female flies. Heat and starvation stress significantly reduced the life span of flies for both sexes. Life-span reduction was more evident in the female flies. Supplementation with CAEE and WAEE showed a profound sex-specific effect on the life span of D. melanogaster under stress. Our results showed that CAEE and WAEE did not increase the life span of male flies but significantly increased the life span of female flies under starvation and heat stress.
Keywords: Auricularia auricula-judae, life span, heat stress, energy deprivation, DPPH assay.